(3Gdbhd GdJGe aj BOGH ONhd GdMeGes - (3TgGH GdOjf CHh GdYHGS CMeO Hf YeGO GdOjf GdCabgSj,J (B808 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH SejJg HGdbhd GdJGe ai BOGH ONhd GdMeGe CPcQ ajg BOGHkG JJYdb HGdOGNd TQYjI hefGaY hCMcGe s
(3BNQgG (B:s
(3bGd ai GdEQTGO hjfHZi dCUMGH GdCeRLI GdMGQI (B,(3gPG BNQ eG jSQ Gddg GdcQje ef Gdbhd GdJeGe ai BOGH ONhd GdMeGe s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg TGaYi Mdje (B13) s
Keywords: (3Gdabg GdTGaYjs